2004
DOI: 10.1016/j.clpt.2004.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Novel genetic variants in Asian subjects and their influence on maintenance warfarin dose

Abstract: Interethnic differences in warfarin dosing in Asian subjects may result from other genetic, dietary, or environmental influences; however, these novel variants in the gene warrant further characterization through functional studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
111
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(117 citation statements)
references
References 35 publications
6
111
0
Order By: Relevance
“…In the present study, we assess the functional consequences of six new alleles recently reported by one of our laboratories (Zhao et al, 2004). These new alleles are as follows: CYP2C9*14 (R125H), CYP2C9*15 (S162X), CYP2C9*16 (T299A), CYP2C9*17 (P382S), CYP2C9*18 (D397A/I359L), and CYP2C9*19 (Q454H).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we assess the functional consequences of six new alleles recently reported by one of our laboratories (Zhao et al, 2004). These new alleles are as follows: CYP2C9*14 (R125H), CYP2C9*15 (S162X), CYP2C9*16 (T299A), CYP2C9*17 (P382S), CYP2C9*18 (D397A/I359L), and CYP2C9*19 (Q454H).…”
Section: Resultsmentioning
confidence: 99%
“…In our recent studies in a Southeast Asian population (59 Chinese, 37 Malay, and 26 Indians), CYP2C9 was sequenced for new mutations (Zhao et al, 2004) including the promoter, 300 base pairs downstream in the 3Ј-untranslated region, the splice-site junctions, and each of the nine CYP2C9 exons. The CYP2C9*2 and CYP2C9*3 alleles were found with varying frequencies in these groups (Indians Ͼ Chinese or Malay).…”
mentioning
confidence: 99%
“…It has been reported that Chinese, Malay and Japanese patients required a 30-40% lower warfarinmaintenance dose than Caucasian patients (Takahashi et al 2003;Zhao et al 2004). These interethnic differences may be attributed to genetic differences.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is well known that there are significant differences in warfarin dose requirement in different ethnic groups; for example, Chinese patients were re- ported to require a warfarin dose nearly 40% lower than that required by Caucasian patients (Zhao et al 2004). In addition, the therapeutic maintenance dose of warfarin for Japanese was also 31% lower than that for Caucasians (Takahashi et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the ethnic differences among patients, it has been shown that Asian populations require a markedly lower warfarin maintenance dose than Caucasians and African-Americans; however, the mechanisms underlying these differences still remain elusive [20,21].…”
Section: Introductionmentioning
confidence: 99%